2023
DOI: 10.1007/s11409-023-09343-0
|View full text |Cite
|
Sign up to set email alerts
|

Scaffolding self-regulated learning from causal-relations texts: Diagramming and self-assessment to improve metacomprehension accuracy?

Abstract: The accuracy of students’ relative comprehension judgments when reading texts is typically rather low. This has been ascribed to students grounding their comprehension judgments on cues that are not diagnostic of their actual comprehension level. Asking students to complete causal diagrams—a diagramming scaffold—before judging comprehension has proved effective in providing them with more diagnostic cues and thereby fostered metacomprehension accuracy and self-regulated learning. However, there is still room f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 66 publications
2
10
0
1
Order By: Relevance
“…Students correctly identified 58.21% of the commission errors, 98.08% of the omission errors, and 74.18% of the correct boxes. These findings are comparable with the findings of Pijeira‐Díaz et al (2023), who found an accuracy of 79% for correct boxes, and of 96% for completed boxes (equivalent to the accuracy of empty boxes/omission errors).…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Students correctly identified 58.21% of the commission errors, 98.08% of the omission errors, and 74.18% of the correct boxes. These findings are comparable with the findings of Pijeira‐Díaz et al (2023), who found an accuracy of 79% for correct boxes, and of 96% for completed boxes (equivalent to the accuracy of empty boxes/omission errors).…”
Section: Resultssupporting
confidence: 91%
“…In sum, we found no significant effects of self‐scoring on monitoring accuracy or text comprehension. This is similar to findings by Pijeira‐Díaz et al (2023); however, in their study, students had to self‐score their diagrams after (delayed) diagramming and did not receive a standard when doing so. Our students were provided with standards, which should give them more insight into the quality of their own diagrams and improve their self‐scoring (and thereby, provide a basis for more accurate monitoring judgements).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Naast het effect van designelementen in een leeromgeving op leerprestaties en motivatie, is er ook veel onderzoek naar wat het voor een student of lerende betekent om in een flexibele leeromgeving te studeren. Onderzoek dat zich op 'self-directed learning' (zie ook: Van Meeuwen et al, 2013), 'self-regulated learing' (zie ook: Pijeira-Díaz, Van de Pol, Channa, & De Bruin, 2023) en andere hogere orde vaardigheden (ook wel 21 ste -eeuwse vaardigheden), zoals 'information-problem solving' (zie ook: Brand-Gruwel & Stadtler, 2011) laat zien dat deze vaardigheden essentieel zijn als studenten de regie over het eigen leerproces geacht worden te nemen in hoog flexibele leeromgevingen (Brand-Gruwel, et al, 2014).…”
Section: Onderzoekunclassified